ANALYSIS OF RAW MATERIAL INVENTORY CONTROL FOR RUMINANT FEED AT PT ANDINI MEGAH SEJAHTERA, BOYOLALI REGENCY, CENTRA JAVA - Aisah Sita Damayanti; Titik Ekowati; Edy Prasetyo (Universitas Sebelas Maret, 2026)
Feed is a vital requirement as a means of livestock production to obtain nutrients in the development process. This study aims to analyze the optimal ruminant feed concentrate raw material inventory, reorder point, safety stock and analyze the comparison of the total cost of concentrate feed inventory before and after using the Economic Order Quantity (EOQ) method at PT. Andini Megah Sejahtera. The research method used is a case study. Data analysis is done by quantitative analysis calculating the optimal raw material inventory through the EOQ method, then comparing with actual conditions and calculating the cost efficiency value of raw material inventory. The results showed that the average order quantity of the most optimal and economical raw material was 351 tons with an average order frequency of 6 times a year. The average amount of safety stock is 235.17 tons and the reorder point is 626.86 tons. A significant difference can be seen between the company's actual total inventory cost and the total inventory cost using the EOQ method. Inventory calculations using the EOQ method can achieve an average inventory cost efficiency of 92% with an average savings of IDR 36,551,229,547 per year. The total inventory cost based on the actual conditions of the company is on average Rp39,194,917,257 greater than using the EOQ method with an average of IDR 643,687,710 per year.